2017
DOI: 10.1017/s174392131800296x
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Photometry with Digitized Photographic Plates of the Moscow Collection

Abstract: Photographic plate archives contain a wealth of information about positions and brightness celestial objects had decades ago. Plate digitization is necessary to make this information accessible, but extracting it is a technical challenge. We develop algorithms used to extract photometry with the accuracy of better than ∼ 0.1 m in the magnitude range 13 < B < 17 from photographic images obtained in 1948-1996 with the 40 cm Sternberg institute's astrograph (30 × 30 cm plate size, 10 × 10 deg field of view) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…We found that the response of the scanner to transmitted light requires an expanded scale, but when that is calibrated out, the data faithfully reproduce values over a density and log intensity range approaching 2.0. Independent scans reduced for stellar photometry are consistent at the fewpercent level, and stars of intermediate brightness near the center of the field are measured for brightness to better than 8% based on matches to Gaia and SDSS photometry, a result that is consistent with Sokolovsky et al (2019).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We found that the response of the scanner to transmitted light requires an expanded scale, but when that is calibrated out, the data faithfully reproduce values over a density and log intensity range approaching 2.0. Independent scans reduced for stellar photometry are consistent at the fewpercent level, and stars of intermediate brightness near the center of the field are measured for brightness to better than 8% based on matches to Gaia and SDSS photometry, a result that is consistent with Sokolovsky et al (2019).…”
Section: Discussionmentioning
confidence: 53%
“…A number of earlier investigations have attempted to use flatbed scanners to digitize astronomical plates, many of which have been concerned with astrometric measurements of stars (e.g., Vicente et al 2007). Other studies have been primarily concerned with photometric measurements (Lamareille et al 2003;Pakuliak et al 2012;Sokolovsky et al 2019). These photometry-focused studies have typically reported internal photometric precision of order 0.1 mag-a result that provides context for our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…An example of a program similar to ours is the scanning effort for the Sternberg Institute's astrograph (Kolesnikova et al 2008;Sokolovsky et al 2017): similar plate scale, field of view, and magnitude limit. These authors also used a flatbed scanner and successfully applied their methods to measure light curves for variable stars on a large time series of plates.…”
Section: Introductionmentioning
confidence: 94%
“…In the first, the pixel values within an individual star image are combined to form a measure (or photometric parameter) that is sensitive to the magnitude of the star, and the nonlinearity in the flux is accounted for by correcting the photometric parameters to match the magnitudes of calibration stars within the field. Examples of this method include Russell et al (1990); Lasker et al (2008); DASCH, Laycock et al (2010); and Sokolovsky et al (2017). In the second approach, the pixel values are corrected before their summation to form a measure of stellar flux guided by some constraint, for example, that the point-spread function should look the same for faint-star profiles and for bright-star profiles.…”
Section: Introductionmentioning
confidence: 99%